Specific HER2 Exon 20 Gly776 Deletion-Insertions in Non-Small Cell Lung Cancer: Structural Analysis and Sensitivity to HER2-Targeted Tyrosine Kinase Inhibitors - Yang, Guangjian; Xu, Haiyan; Hu, Jiaqi; Liu, Runze; Hu, Peizeng; Yang, Yaning; Li, Weihua; Hao, Xuezhi; Zhang, Shuyang; Xu, Fei; Ai, Xin; Li, Junling; et al. (Frontiers in Pharmacology, 2022)
Background: HER2 exon 20 insertions remain a subset heterogeneous alterations in lung cancer, with currently unmet need for precision targeted therapy. G776delinsVC, a typical HER2 exon 20 deletion-insertion at codon Gly776, was reported to respond discrepantly to afatinib compared with the predominant insertion A775_G776insYVMA (YVMA). However, it lacks structural evidence to illustrate the possible mechanism and predict the binding activities of its similar variants over YVMA insertion to HER2-targered tyrosine kinase inhibitors (TKIs). Methods: Real-world cohort study was performed to investigate clinical outcomes with HER2-targeted TKI afatinib and pyrotinib, and structural analysis for exon 20 Gly776 deletion-insertions G776delinsVC, G776delinsLC and G776delinsVV, and YVMA by molecular dynamics simulation and cellular kinase inhibition assay were provided for full exploration. Results: Afatinib revealed low objective response rate (ORR) of 0-9.5% and short median progression-free survival (mPFS) of 2.8-3.2 months for YVMA, but with higher ORR of 20%-28.6% and longer mPFS of 4.3-7.1 months for G776delinsVC. Pyrotinib presented significantly improved PFS benefit for G776delinsVC and YVMA as first-line (median, 6.8 vs. 3.4 months, P=0.010) or second-line therapy (median, 5.8 vs. 2.8 months, P˂0.001). No significant difference was observed on drug binding pocket and TKI binding activity between G776delinsVC, G776delinsLC and G776delinsVV, and both afatinib and pyrotinib showed favorable binding activity. YVMA insertion significantly affected the loop region with altering HER2 protein secondary structure and forming steric hindrance to binding of afatinib. Pyrotinib showed the best selectivity to HER2, with more favorable activity to YVMA than afatinib indicated by cellular inhibition assay. Conclusion: Both afatinib and pyrotinib showed favorable activity for NSCLC patients with HER2 exon 20 Gly776 deletion-insertions. Pyrotinib revealed more potent activity to A775_G776insYVMA insertion than afatinib due to the steric binding hindrance of induced by YVMA.